Histamine and histamine-forming bacteria in keropok lekor (Malaysian fish sausage) during processing - Nor-Khaizura M.A.R.; Zaiton H.; Jamilah B.; Rusul R.A.G.; Ismail-Fitry M.R. (2024)
Indexed by SCOPUS/WOS